Etiological explanations of Psychosis - Sparrow, César (1999)
Although the entire origin of the psychoses is still unknown, are shown fundamental neurobiological aspects, recognizing the factor of heredity. Even though, mostly half the question about the ethiology of psychoses remams unsolued. The explorations of psychoanalysis try to fill this blank. Are remarked the conceptions of their main representative: S. Freud .M. Klein, J. Lacan. Finally, are indicated some considerations about the somatic-psychic, the idea of mental health, sanity or normality, and a reach of modern scientific researchs on human consciousness related to quantum physics.